Long term outcomes for adults with complete atrioventricular septal defects. (14th October 2021) - Seitler, S; Al-Sakini, N; Lacerna, A; Flick, C; West, C; Senior, R; Gatzoulis, M A; Li, W
Abstract: Background/Introduction: Complete Atrio-Ventricular septal defect (AVSD) is a complex congenital cardiac disease, characterised by malformation at the atrio-ventricular junction and AV valve abnormalities. Long- term outcome data is limited. Purpose: We sought to describe the long-term outcomes of adults with repaired complete AVSD in a tertiary adult congenital heart centre. Methods: We retrospectively recruited patients with complete AVSD who underwent surgical repair between 1973 and 2001 in our centre. All clinical and echocardiographic data were collected and analysed for evidence of atrio-ventricular valve (AVV) deterioration, or cardiac dysfunction. We also assessed for the requirement for further surgical intervention throughout the follow up period. Results: A total of 345 patients with AVSD were identified, partial AVSD 211, unrepaired 82. Fifty-two with repaired complete AVSD formed study group, female 36 (69%) and male 16 (31%), Trisomy 21 (23, 44%). Mean age at initial repair was 44 months (median 12, IQR 31.5). Mean follow up was 25.3 years (Median 24, IQR 9.75). Clinical status: At the latest follow-up, most patient were asymptomatic with NYHA I-II (n=46) Majority (n=36, 69%) required only initial repair and no further intervention. Further surgeries were performed in 16 patients including AVV repair (n=9) and LVOTO relief (n=3). Permanent pacemaker insertion needed in 6 (12%), all for heart block following valve repair. 7 patients (14%) had documented arrythmia, 4 (8%) requiring ablations and only 1 had endocarditis. Echo findings: AV Valve dysfunction was more commonly regurgitant rather than stenotic. More than moderate AVV regurgitation was present in 83% of patients, Left AVV (n=25, 48%), Right AVV (n=18, 35%) compared to 4% stenosis (LAVV n=1, RAVV n=1). Ventricular outflow tract obstruction was present in 8% of patients, RVOT obstruction (2, one native, one secondary to prior banding), LVOT obstruction (2, both native, one requiring surgical intervention). Right ventricular systolic dysfunction was present in 6% of patients (n=3), with mean TAPSE 14.1mm (SD± 3.1mm). Left ventricular dysfunction was present in 4% (n=2), mean LVEF 58.9% (SD±7.1%) and mean LV EDVi 55.06mL/m 2 (SD±13.2 mL/m 2 ). Only one patient had significant pulmonary hypertension (Mean PAP 48 mmHg). Conclusion: Long-term outcomes of surgically repaired AVSD are highly favourable. Left AVV regurgitation is the most common residual lesion requiring further surgical intervention. Ventricular outflow tract obstruction was much less common, as was ventricular systolic dysfunction. Complete heart block was associated with surgical repair and arrhythmias were potential late complications. FUNDunding Acknowledgement: Type of funding sources: None.